A measurement of the muon number in showers using inclined events recorded at the Pierre Auger Observatory - Allekotte, Ingomar; Almela, Daniel Alejandro; Bertou, Xavier Pierre Louis; Dova, Maria Teresa; Figueira, Juan Manuel; Filevich, A.; Garcia, Beatriz Elena; Gomez Berisso, Mariano; Gómez Vitale, Primo F.; González, N.; Hansen, P.; Tueros, Matias Jorge; et al. (Sociedade Brasileira de Fisica, 2014)
Fil: Allekotte, Ingomar. Centro Atómico Bariloche and Instituto Balseiro; Argentina